A pontine tuberculoma mimicking an exophytic brain stem tumor - (:unkn) unknown (My University, 1993)
A 21 year old man with a five month history of facial paresis, diplopia, and gait disturbance diagnosed with a brain stem tumor at another institution was evaluated. Computed tomography, magnetic resonance imaging, clinical and laboratory evaluations suggested a pontine astrocytoma, and the mass was excised. Pathological diagnosis was a tuberculoma confirmed by postoperative positive Mantoux testing. CT and MRI appearances of tuberculomas have been described, but can not differentiate them completely from other tumors such as astrocytomas. Because the incidence of tuberculomas has increased in recent years and they may mimic exophytic tumors of pons, it is important to include pontine tuberculoma in the differential diagnosis of pontine tumors.
Keywords: Adult; Humans; Male; Pons; Magnetic Resonance Imaging; Brain Neoplasms; Drug Therapy, Combination; Combined Modality Therapy; Contrast Media; Diagnosis, Differential; Antitubercular Agents; Tuberculosis; Neurologic Examination; Brain Stem; Gadolinium DTPA; Organometallic Compounds; Pentetic Acid; Tuberculoma